THE USE OF RIPOLIN BY PICABIA IN THE FIG LEAF (1922). Issue 4 (November 2013) - King, Annette; Townsend, Joyce H.; Ormsby, Bronwyn; Gautier, Gwénaëlle
<x content-type="archive" xml:space="preserve">Abstract</x> From both anecdotes and the appearance of many works, Francis Picabia—like Pablo Picasso—is believed to have used Ripolin house paint. La Feuille de Vigne(The Fig Leaf) (1922 Tate), variously described as painted in enamel, oil, and Ripolin, has many visual characteristics associated with household paint: large areas of unmodulated color, minimal evidence of brushstrokes, and a glossy surface. An earlier work, Les Yeux Chauds(Hot Eyes) of 1921, was already known to exist beneath the surface. A study of documentary sources on Picabia was combined with an exploration of this earlier image through extensive technical examination, which identified paint characteristics, including the presence of Ripolin paints in both, and accounted for strikingly obvious localized wrinkling in areas of The Fig Leaf. The color range of Les Yeux Chauds was found to consist of bold complementary colors, not black and white as previously assumed. The evolution of the two images is explored, and both Picabia's techniques and his use of specific materials are discussed; the materials in both paintings correspond closely to referenced Ripolin samples. Examination revealed a playful relationship between the two images painted by Picabia, and has contributed new evidence about the lost image of Les Yeux Chauds.